(untitled) (Zaporizhzhia Historical Review, 2021)
The article deals with the main trends of politically organized national revolt (resistance) movement in the 20s of the XX century in the Naddniprovskaya region. The author regards the transition process from the revolution methods of struggle to the postrevolution ones. He pays great attention to the Ukrainian military organization.